Formation and development of students’ technological competence in the process of research-based learning via foreign language environment immersion by means of informatized educational process: empirical studies - Hrybiuk, Olena; Vedishcheva, Olena; Nachuichenko, Kateryna; Panchyshyn, Oleksander; Levchuk, Viktoria; Kovalenko, Tamara; Danyliuk, Tetyana; Sysiuk, Zoya; Ivaniuk, Anton (ScienceRise: Pedagogical Education, 2020)
The investigation thoroughly represents the possibilities of pedagogical designing with pedagogically balanced use of variable models of computer-oriented methodological systems of research-based learning of natural and mathematical disciplines in schools in the context of continuity of education. In the framework of the research-experimental work “Formation of students’ technological competence via foreign language environment immersion by means of informatized educational process”, programmers of optional courses were worked up and classes were held. The hypothesis that teaching children determines the nature of their mental development is confirmed. Accordingly, the characteristics which are necessary and sufficient for the organization of research education at school, including the use of information and communication technologies and taking into account the psychological and pedagogical characteristics of students in the process of computer-based methodological systems of research-based learning are thoroughly described. The purpose of the study is to identify the potential of the English language in order to form the technological competence of students to increase the effectiveness of teaching subjects of the natural-mathematical cycle, the intellectual development of students and the formation of persistent cognitive interests using informational and communicational technologies. The technique of immersion in a foreign language environment COMSRL is used, providing the teaching of the natural-mathematical cycle subjects in English. The experimental study identified three options for the use of computer technology in education: monotechnology, basic technology, penetrating technology. Penetrating technology is used in the basic training of students. The use of the English language for the formation of students’ technological competence in the process of research teaching creates an opportunity to increase motivation in the context of studying other subjects and the English itself, develops potential and creativity, activates cognitive activity, increases independence and initiative in acquiring new knowledge in technological competencies, creates conditions for professional self-determination and development of students. Based on a thorough analysis of the research results, the need to distinguish between different gifted groups of students is confirmed, as there are different aspects of giftedness (high intellectual giftedness and high level of academic success, etc.) and different group differences. Students with a migrant background often face difficulties in adjusting to a new learning environment. Education and training practitioners can benefit from guidance and the sharing of good practices to be able to address the learning needs of students in increasingly diverse and multilingual classrooms. The investigation thoroughly represents three priorities for education: to integrate newly arrived migrants into mainstream education structures as early as possible; to prevent underachievement among migrants; to prevent social exclusion and foster intercultural dialogue